การพัฒนาแนวทางสำหรับการควบคุมกระบวนการโดยใช้แผนภูมิควบคุมในกระบวนการผลิตแผ่นลายวงจรชนิดอ่อน - ศิรินทรา ทันอินทรอาจ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The objective of this research is to develop the guideline for controlling processes with the control charts in flexible printed circuit manufacturing. An important problem in control chart implementation is the design of control chart to yield the best value and benefits to the organization. There are five steps proposed in the guideline. First, the parameters to control were selected and prioritized based on the technical and the cost criticality. Second, the processes to control were prioritized based on the relationship with process parameters using the matrix diagram. Third, the type of control charts, the sampling frequency and the sample size were determined. Fourth, the benefit to cost ratio of the control chart implementation was calculated to present the value of the control chart implementation. Fifth, the criteria for control limits revision were identified. This research used the developed guideline in the case study factory and found that 7 out of 51 parameters should be monitored with control charts. The benefit to cost ratio of the variable control chart and the attribute control chart implementation were 10.75 and 3.55, respectively. Thus, it was worth for the organization to implement the control charts.